1, 1‐Diphenylvinylsulfide as a Functional AIEgen Derived from the Aggregation‐Caused‐Quenching Molecule 1, 1‐Diphenylethene through Simple Thioetherification. (30th December 2019) - Wang, Bo‐Wen; Jiang, Kai; Li, Jian‐Xiao; Luo, Shi‐He; Wang, Zhao‐Yang; Jiang, Huan‐Feng
Abstract: An efficient and readily scalable thioetherification between 1, 1‐diphenylethene (DPE) and sodium arylsulfinate was developed for the synthesis of 1, 1‐diphenylvinylsulfide (DPVS) with the yield up to 99 %. The photophysical properties of DPVS show that the introduction of arylsulfenyl groups onto the parent molecule DPE makes DPVS a novel type of aggregation‐induced emission (AIE) luminogen (AIEgen) with large Stoke's shift (up to 188 nm). These DPVS possess AIE properties due to restriction of intramolecular motions (RIM), as demonstrated by crystal structure analysis. Importantly, the AIE performance of DPVS can be applied to sense the nitroaromatic explosive picric acid in aqueous systems through a "turn‐off" response. Abstract : Die Thioveretherung zwischen 1, 1‐Diphenylethen (als Baustein für aggregationsinduzierte Emission) und Natriumsulfinaten bietet einen neuen Weg für die Umwandlung von Verbindungen mit aggregationsbedingter Löschung (ACQ) in AIE‐Luminogene. Unter milden Bedingungen ohne zusätzliches Oxidationsmittel liefert die Reaktion eine Ausbeute von bis zu 99 % und ermöglicht den Zugang zu trisubstituierten Ethenen als AIE‐Luminogene für Sensoranwendungen.